Factors affecting work-life balance and psychological resilience levels of nurses working in internal clinics during COVID-19 - Korkmaz Aslan, Tuba; Burucu, Rukiye; Akdoğan, Yunus (Publishing Office of the University of Rzeszow, 2023)
Introduction and aim. COVID-19 intensity has affected both the psychology of the nurses and the balance established between their work and social lives. In this study, it was aimed to examine the work-life balance and psychological resilience levels of nurses. Material and methods. Four Hundred and seventy two nurses, working in various hospitals and internal units in Turkey, voluntarily participated in the study. Data was collected online using the Work-Life Balance Scale, Brief Psychological Resilience Scale, and the Personal Information Form. Results. The sub-dimensions of the work-life balance scale include allocation of time for yourself (β=1.892; p<0.001), life merely being based on work (β=-0.513; p<0.05) and work-life balance; affect the psychological resilience score (β=-0.364; p<0.05). Based on this, devoting time for yourself has a positive effect on psychological resilience, while others have a negative effect. The total score of the nurses on work-life balance is 51.51±7.22 and their psychological resilience score is 15.27±3.93. Conclusion. Psychological resilience is affected by educational status, marital status, having children, and working schedule; work-life balance is affected by educational status, marital status, having children, income levels, and working schedule; while work-life balance sub-dimensions are affected by education, marital status, having children, income levels, place of work and working schedule. Both work-life balance and its sub-dimensions affect the psychological resilience of nurses.
Ethical approval and informed consent were obtained (2021-02-17T20_50_25 and 03.03.2021, Decision Number: 06).
Keywords: COVID-19; nursing; psychological resilience; work-life balance